Da Livio a Machiavelli. Annibale e Scipione in "Principe", XVII - Jean-Jacques Marchand (Parole Rubate, 2016)
In the classical tradition (and especially in Livy’s work), Hannibal and Scipio are described as two generals who have confronted each other in a titanic struggle with alternate fortunes for the control of the Mediterranean. Focusing on the superiority of cruelty over pity for the safety of the state, in the seventeenth chapter of Il Principe Machiavelli contrasts the greater efficiency of Hannibal’s cruelty with Scipio’s mildness. This article examines the techniques of shifting, coagulation, and relocation adopted by Machiavelli in his approach to three passages from the Livian text which constitute the source of the chapter.